2016
DOI: 10.2298/fuee1601049m
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pulsed negative bias temperature stressing in p-channel power VDMOSFETs

Abstract: Our recent research of the effects of pulsed bias NBT stressing in p-channel power VDMOSFETs is reviewed in this paper. The reduced degradation normally observed under the pulsed stress bias conditions is discussed in terms of the dynamic recovery effects, which are further assessed by varying the duty cycle ratio and frequency of the pulsed stress voltage. The results are analyzed in terms of the effects on device lifetime as well. A tendency of stress induced degradation to decrease with lowering the duty cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…NBT stress-induced threshold voltage instabilities in commercial power VDMOSFETs, as well as the implications of related degradation on device lifetime have been extensively investigated in our research in the last decade [27,[42][43][44]. Although in many experiments devices have been subjected to various NBT stress (static or pulsed) and annealing conditions [9,23,25,45,46,[48][49][50][51][52], in this section a part of results obtained during static NBT stress and annealing is presented, with attention to insight into the NBTI as a result of sequential NBT stress and bias annealing steps.…”
Section: Nbt Stress Effectsmentioning
confidence: 99%
“…NBT stress-induced threshold voltage instabilities in commercial power VDMOSFETs, as well as the implications of related degradation on device lifetime have been extensively investigated in our research in the last decade [27,[42][43][44]. Although in many experiments devices have been subjected to various NBT stress (static or pulsed) and annealing conditions [9,23,25,45,46,[48][49][50][51][52], in this section a part of results obtained during static NBT stress and annealing is presented, with attention to insight into the NBTI as a result of sequential NBT stress and bias annealing steps.…”
Section: Nbt Stress Effectsmentioning
confidence: 99%
“…According to available literature, it seems that at the moment application of Python in measurements is the most popular in advanced scientific experiments. Examples of applications which might find approach proposed in this paper useful are [28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that the results regarding the SiO 2 and SiO 2 -Si interface published so far are of importance since they contribute to the process of determining the nature of the oxide and the interface defects. These defects were mostly responsible for the effects of irradiation, accelerated testing, high electric field stress (HEFS), and bias temperature (BT) stress, [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] observed in power MOS transistors, as well. There is particular interest in research of reliability and effects induced by harsh conditions during operation of novel power vertical double-diffused MOS (VDMOS) transistors in different applications.…”
Section: Introductionmentioning
confidence: 99%
“…This interest has continuously risen during the last decades. [20][21][22][25][26][27][28][29][30][31][32][33][34][35][36][37] The results have shown that ionizing irradiation may reduce system lifetime that could be caused by degradation of several electrical parameters of power MOS transistors, especially threshold voltage (V T ) as the most important one. It should be noted that negative threshold voltage shift (ΔV T ) induced by radiation is the most critical reliability problem since it may cause change of operation mode from enhancement to depletion in n-channel power MOS transistors or dramatically reduction of current driving capability in p-channel ones.…”
Section: Introductionmentioning
confidence: 99%